2016
DOI: 10.1590/1983-21252016v29n210rc
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Diazotrophic Bacteria and Nitrogen Fertilization in Topdressing in Irrigated Corn

Abstract: -Corn is a nitrogen-intensive crop, and the use of management practices such as inoculation of the seed with diazotrophic bacteria, which can maximize crop productivity and reduce the need of nitrogen fertilizers, may result in lower production costs. The present study aimed to evaluate the effect of inoculation of corn seed with Azospirillum brasilense and controlled addition of nitrogen to topdressing on the nutrition, production components, and productivity of crop grain. The experimental design was a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The lack of application of nitrogen fertilizer during the spring, added to a single low dose (70 kg N/ha) only in January, would have generated a condition of low N availability and, in effect, contributed to the longevity of the tiller population. This same pattern of response had already been reported by Costa et al (2016) and Pessoa et al (2016), who evaluated the tiller dynamics of Marandu palisadegrass under conditions of low nitrogen fertilizer application (50 and 60 kg N/ha during the entire rainy season, respectively) and observed TSR values above 80% from winter to summer. However, despite the relevance of TSR for the persistence of Marandu palisadegrass, it is important that management practices ensure high TAR in early spring (October), a time when this forage plant regains its tiller population density (Costa et al 2016;Pessoa et al 2016).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The lack of application of nitrogen fertilizer during the spring, added to a single low dose (70 kg N/ha) only in January, would have generated a condition of low N availability and, in effect, contributed to the longevity of the tiller population. This same pattern of response had already been reported by Costa et al (2016) and Pessoa et al (2016), who evaluated the tiller dynamics of Marandu palisadegrass under conditions of low nitrogen fertilizer application (50 and 60 kg N/ha during the entire rainy season, respectively) and observed TSR values above 80% from winter to summer. However, despite the relevance of TSR for the persistence of Marandu palisadegrass, it is important that management practices ensure high TAR in early spring (October), a time when this forage plant regains its tiller population density (Costa et al 2016;Pessoa et al 2016).…”
Section: Discussionsupporting
confidence: 85%
“…It is important that stockpiled pasture grows rapidly in spring and summer (Santana et al 2014;Santos et al 2020), and the response depends on its ability to emit new tillers (Colvill and Marshall 1984), as tiller numbers in pasture are a reflection of the balance between birth and survival rates of tillers (Costa et al 2016;Pessoa et al 2016;Duchini et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…O N participa diretamente na síntese da clorofila e ainda exerce papel importante na síntese de enzimas (PEPC e Rubisco), que participam da fixação no CO 2 atmosférico (Prado, 2008). Assim, a menor disponibilidade de N para as plantas pode reduzir as concentrações de clorofila a e b (Akram, 2014;Longhini et al, 2016), contribuindo para a menor taxa fotossintética e consequentemente, menor crescimento, em função da importância desses pigmentos para a absorção de fótons e para o transporte de elétrons (Buchanan;Gruissem;Jones, 2015).…”
Section: Resultsunclassified
“…In addition to the high value crops exploration, the possibility of using new technologies, aimed at increasing the quality of the material produced, can be considered. In this perspective, it is observed the introduction of diazotrophic bacteria, which can perform the biological fixation of atmospheric nitrogen in grasses, through the enzyme nitrogenase (3), culminating in positive growth effect on maize plants, for example (4). It is also observed that the inoculation with these bacteria is a low-cost technique, when its participation in the total operational cost of production is verified (5,6).…”
Section: Introductionmentioning
confidence: 99%